AN ANALYSIS OF IRONY USED IN WEDNESDAY ADDAMS SERIES - Alvina Amalia Puteri; Vera Kristiana (PHILOLOGY Journal of English Language and Literature, 2023)
In this thesis entitled An Analysis of Irony Used in Wednesday Addams Series, researchers will examine the existence the types of irony and the meaning contained in it. This research uses qualitative descriptive method. This drama series was chosen because there are many sentences that contain ironic language styles in it. The theory used to analyze the data uses semantic theory. The purpose of this research is to analyze irony sentences and then classify them based on the meaning they have so that they can produce certain types of irony. After analyzing the data, there are three types of irony, namely Verbal irony, Situational irony and Drama irony found in conversations and character interactions in each drama series.